Ethnic variability in post‐mastectomy breast reconstruction in Counties Manukau District Health Board in 2017: a retrospective review. Issue 7 (14th May 2020) - Allan, Jessica; Locke, Michelle; Wagener, Jenny
Abstract: Background: Post‐mastectomy breast reconstruction (PMBR) is associated with greater quality of life and psychological well‐being. However, rates of PMBR may not be equivalent across all ethnicities which contributes to disparities in health outcomes. Methods: A retrospective review of patients diagnosed with breast cancer between 1 January and 31 December 2017 at Counties Manukau District Health Board (CMDHB) was performed. Data regarding patient demographics, cancer stage, breast cancer treatment and whether reconstruction took place were collected. These data were analysed to assess the rates of reconstruction by ethnic group. Results: A total of 365 patients were diagnosed with cancer in CMDHB breast cancer clinic in 2017. Of these, 177 were treated with mastectomy and 26 (15%) of these patients received PMBR. Thirty‐four percent of patients receiving mastectomy were of Māori or Pasifika ethnicity. Of these patients, one‐third met the eligibility criteria for PMBR at CMDHB, having body mass index <35 and being non‐smokers. Māori women represented only 4% of the PMBR performed at CMDHB in 2017. European women comprised 50% of all mastectomies but received 77% of all PMBR. There was a significant difference in eligibility between the different ethnic groups for PMBR, due to higher body mass index and higher rates of smoking in Māori and Pasifika patients. Conclusion: Eligibility rates for post‐mastectomy reconstruction are significantly lower ( P < 0.05) in Māori and Pasifika women when compared with European and Asian populations. Strategies to address smoking and obesity may help increase rates of PMBR in Māori and Pasifika women. Abstract : In this study, we present a retrospective review of 365 patients diagnosed with breast cancer in Counties Manukau District Health Board in 2017 and their treatment. We found a significant difference in eligibility between Māori and Pasifika women for post‐mastectomy breast reconstruction contributing to lower rates of post‐mastectomy breast reconstruction in these populations.